THE INFLUENCE OF PRINCIPLES OF CHARACTER, CAPITAL, COLLATERAL, CAPACITY, CONDITION OF ECONOMY ON THE SMOOTHNESS OF MURABAHAH FINANCE PAYMENTS AT PT. BPRS PUDUARTA INSANI - Salman Ritonga; Nur Ahmadi Bi Rahmani (Jurnal Ekonomi, 2023)
This study aims to see the effect of character, capital, collateral, capacity, and economic conditions on the smoothness of murabahah financing payments to customers of PT. Bank BPRS Puduarta Insani. Judging from the NPF value, this bank is stated to be healthy and able to maintain the stability of the company with the ability to analyze financing to customers properly. The method used in this study is the quantitative method, the data is distributed using the help of a Likert scale questionnaire, the analysis test is carried out using the classical assumption test and the hypothesis test is loaded with the help of SPSS 25. From the results of the tests carried out, it is found that simultaneously the character, capital, collateral, capacity, and condition of economy have a significant effect on the smoothness of murabahah financing payments.